VARIABEL – VARIABEL YANG MEMPENGARUHI NILAI PERUSAHAN MAKANAN DAN MINUMAN (Studi Pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia) - Rizky Widi Saputra; Harlen dro (Jurnal Ilmiah Mahasiswa FEB, 2013)
The creation of firm value can provide a positive impact to  the owner of the company or  shareholders. The purpose of this research is to examine the influence of  firm size, profitability, assets growth, sales growth, capital structure and  risk financial  to  the firm value  which is proxied to  price-book value.  The population in this study is a  food and beverage  company that is listed on the Indonesia Stock Exchange during the period 2009 to 2012. Samples were taken by purposive  sampling technique that is based on specific criteria, so obtained a sample of corporate data 12  food and beverage companies. Tested in this study used multiple regression analysis. From the results of multiple regression analysis known that  firm size, profitability, assets growth, sales growth, capital structure and risk financial simultaneously affect firm value. Profitability, capital structure and  risk financial  has  positive  effect  and significant  on firm value, with assets growth  has negative effect and significant  on firm  value. Besides firm size and sales growth has negative effect on firm value significantly.   Keywords:  Firm Value, Firm Size, Profitability, Assets Growth, Sales Growth, Capital Structure, Financial Risk.